Fluorine-containing acrylate emulsion as well as preparation method and application thereof

By copolymerizing the fluorine-containing acrylate polymer emulsion with core-shell structure with other acrylate monomers, the problems of insufficient hydrophobic properties and poor adhesion of fluorine-containing acrylate polymer emulsion in the prior art are solved, and high adhesion and low adhesion are achieved The coating is at the cost and the hydrophobicity of the coating is enhanced by the modified polymer emulsion, achieving superhydrophobic effect.

CN119320477APending Publication Date: 2025-01-17NANJING UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411564147.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing fluorine-containing acrylate polymer emulsions have problems such as insufficient hydrophobic properties, poor adhesion and large environmental pollution. In particular, short fluorocarbon chain polymers are difficult to be stable on the surface of the material, and long fluorocarbon chain polymers accumulate in the environment to create potential. risk.

Method used

The fluorocarbon acrylate polymer emulsion with core-shell structure is prepared by introducing fluorocarbon chain short monomers and copolymerizing with other acrylate monomers, reducing surface free energy and improving adhesion, while using water as a solvent and a specific emulsifier. It has excellent hydrophobic properties and low cost coating.

Benefits of technology

The adhesion and hydrophobic properties of the coating are significantly improved, while reducing production costs, achieving economic and functional coexistence, and the hydrophobicity of the coating is enhanced by modifying polymer emulsions to achieve superhydrophobic effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320477A_ABST
    Figure CN119320477A_ABST
Patent Text Reader

Abstract

The invention discloses a fluorine-containing acrylate polymer emulsion and a preparation method and application thereof.The preparation method comprises the steps that under the action of an initiator and an emulsifier, water serves as a solvent, methyl methacrylate and butyl methacrylate are polymerized to form a nuclear phase, and then under the action of the initiator and the emulsifier, a fluorine-containing acrylate polymer emulsion is obtained; methyl methacrylate, butyl methacrylate, octadecyl methacrylate, hydroxyethyl methacrylate and fluorine-containing methacrylate are subjected to a polymerization reaction to obtain a fluorine-containing acrylate polymer emulsion, and the prepared polymer emulsion is degradable, contains a short fluorocarbon chain and has excellent hydrophobic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer emulsion, in particular to a fluorine-containing acrylic ester emulsion and a preparation method and application thereof, belonging to the technical field of chemical industry. Background Art

[0002] Surfaces with ideal wetting properties have received extensive attention in both basic research and practical applications. The wetting properties of solid surfaces are determined by the surface energy and microscopic roughness of the solid surface. Inspired by the super-hydrophobic plant surfaces in nature, such as the lotus leaf surface, researchers have found that super-hydrophobic surfaces can be achieved by reducing the surface free energy to provide hydrophobicity or constructing micro-nano structures.

[0003] Fluoropolymers have low surface energy on most substrates, thus endowing the treated substrate surface with good hydrophobicity and oleophobicity. In addition, they have liquid corrosion resistance, stable weather resistance and excellent mechanical properties, making them candidates for constructing superhydrophobic surfaces. Among the many fluoropolymers, fluoroacrylate (FA) polymers have received extensive attention due to their high hydrophobicity, good film-forming properties and strong adhesion on various substrates.

[0004] Fluorinated acrylate monomers can undergo good copolymerization reactions with other monomers, which not only maintains their inherent excellent properties, but also greatly reduces their production costs. The low crystallinity, good solubility, and easy molding and processing characteristics of their copolymers also make their application range far greater than other acrylic polymers. The widely used fluorinated acrylate polymers are mainly fluorinated (meth) acrylate polymers with long fluorocarbon chains (carbon number ≥ 8) (such as perfluorooctyl methacrylate). This is because the longer fluorocarbon segments have strong mobility, the polymer is easy to crystallize, and the -CF3 group with very low surface energy is easy to migrate to the surface, making the material have good hydrophobic and oleophobic properties. However, perfluorooctyl-containing polymers can be degraded into functional perfluorooctyl-containing compounds, which will accumulate in the environment and in organisms, causing potential risks, and their synthesis process is complicated. Compared with fluorinated polymers with long fluorocarbon chains, fluorinated acrylate polymers with short fluorocarbon chains (carbon number ≤ 6) have good degradability and have received widespread attention. However, short fluorocarbon chains have low crystallinity and are difficult to migrate and stably arrange on the surface of materials, and have poor adhesion, so their hydrophobic and oleophobic effects are insufficient; a Chinese patent application document with publication number CN104788608A discloses a fluorinated copolymer for low-energy surface coatings, which specifically uses butyl methacrylate (BMA) and fluorinated acrylate to polymerize to obtain a fluorinated copolymer, which introduces acrylate monomers and copolymerizes with them so that the fluorinated groups can be stably attached to the surface, thereby achieving good hydrophobic and oleophobic effects; however, its attachment is mainly achieved through the physical attachment of acrylate polymers and the use of too high an amount of fluorinated monomers leads to increased costs, and its solution polymerization uses organic reagents as solvents, which causes greater environmental pollution.

[0005] The contact angle of acrylate polymers on substrates is limited to a maximum of 120°. Therefore, it is necessary to construct micro-nanoscale roughness on the polymer surface to increase its contact angle. In recent years, spray deposition technology has attracted attention as a method to increase surface roughness because of its advantages such as rapidity and easy scale-up. With the development of this technology, organic / inorganic nanoparticles have attracted more and more attention from researchers. Among inorganic nanoparticles, silica is the most widely used in research and industry. There are two main methods for preparing polymer / silica composite particles. One is to introduce vinyl-containing monomers for copolymerization, and the other is to simply mix nano-silica and polymers. The research on preparing polymer / silica composite particles to increase the contact angle of the polymer surface has become a hot topic. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a degradable fluorinated acrylate polymer emulsion containing short fluorocarbon chains and excellent hydrophobicity, as well as a preparation method and application thereof, so as to overcome the defects of the existing fluorinated polymer emulsion.

[0007] In order to solve the above technical problems, the present invention provides a fluorinated acrylate polymer emulsion, which has a core-shell structure, and its core phase is a polymer having a general chemical structure formula:

[0008]

[0009] Wherein, R is hydrogen or methyl, R1 is selected from any one of C1 to C18 alkyl groups, m=any integer from 30 to 80, and n=any integer from 10 to 30;

[0010] The shell phase is a polymer with the following chemical structure:

[0011]

[0012] Wherein, R is hydrogen or methyl, R1 is selected from any one of C1~C18 alkyl groups, R2 is selected from any one of C12~C18 alkyl groups, Rf is a group having a C(CF3)2CF2CF2CF3 structure, m=any integer from 10 to 100, n=any integer from 10 to 100, a=any integer from 5 to 15, b=any integer from 1 to 10, and c=any integer from 2 to 30.

[0013] Technical effect: The fluorinated acrylate polymer emulsion disclosed in the present invention combines with the surface of the substrate using active groups, which significantly enhances the adhesion of the resulting coating while maintaining excellent hydrophobic properties, and the cost is further reduced.

[0014] The technical solution further defined in the present invention is:

[0015] Furthermore, in the aforementioned fluorinated acrylic polymer emulsion, the polymer weight average molecular weight is 1.7×10 5 ~3.5×10 5

[0016] The present invention also provides a method for preparing a fluorinated acrylic polymer emulsion, which specifically comprises the following steps:

[0017] Under the action of initiator and emulsifier, water is used as solvent, and the The two acrylic ester monomers are polymerized into a core phase polymer, and then under the action of an initiator and an emulsifier, the core phase polymer is expressed as and The acrylic acid ester monomer is represented by Hydroxyethyl acrylate and represented by The fluorinated acrylate monomer is polymerized on the surface of the core phase polymer to form a shell phase polymer, thereby obtaining a fluorinated acrylate polymer emulsion with a core-shell structure.

[0018] The technical solution further defined in the present invention is:

[0019] Further, in the preparation method of the aforementioned fluorinated acrylate polymer emulsion, it is represented by The acrylic acid ester monomer is selected from any one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hexyl methacrylate, isooctyl methacrylate, lauryl methacrylate, octadecyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, hexyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate.

[0020] In the above-mentioned method for preparing the fluorinated acrylic polymer emulsion, it is represented by The acrylic acid ester monomer is selected from any one of lauryl methacrylate, octadecyl methacrylate, lauryl acrylate and octadecyl acrylate.

[0021] In the preparation method of the fluorinated acrylic polymer emulsion, the initiation temperature is 30-100° C., the polymerization temperature is 30-200° C., and the time is 5-20 hours.

[0022] In the preparation method of the above-mentioned fluorinated acrylic polymer emulsion, the amount of the initiator used is 0.1-5% of the total weight of the acrylic monomer; the initiator is a mixture of one or more of azo compounds, organic peroxides, and inorganic peroxides; the emulsifier is selected from at least one of anionic emulsifiers, nonionic emulsifiers, and cationic emulsifiers.

[0023] In the above-mentioned method for preparing the fluorinated acrylic polymer emulsion, it is represented by The acrylic acid ester monomer is selected from octadecyl methacrylate, and the weight ratio of the fluorinated methacrylate monomer to octadecyl methacrylate is 1:1-1:5; the mass ratio of the fluorinated methacrylate monomer to hydroxyethyl acrylate is 20:7-100:7.

[0024] In the above-mentioned method for preparing the fluorinated acrylic polymer emulsion, it is represented by The fluorinated acrylate monomer is prepared in the presence of a base. Obtained by reaction, X is a halogen;

[0025] in: The molar ratio of the base is 1:(1-1.5):(1-1.5).

[0026] In the above-mentioned method for preparing the fluorinated acrylic polymer emulsion, the base is an organic base, and the organic base is selected from any one of triethylamine, pyridine, N,N-diisopropylethylamine, diethylamine, piperidine or N-methylpiperidine;

[0027] The reaction temperature is -30°C to room temperature (preferably -10°C to 0°C), and the reaction solvent is any one of ethylene glycol dimethyl ether, ethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, dichloromethane, DMF, benzene or 1,2-dichloroethane.

[0028] The present invention also provides an application of a fluorinated acrylate polymer emulsion, wherein the fluorinated acrylate polymer emulsion is applied to prepare a coating:

[0029] The prepared fluorinated acrylic polymer emulsion is mixed with silica sol and isocyanate curing agent, and uniformly dispersed in ultrasound to obtain a silica sol-modified polymer emulsion, which is then coated to form a coating.

[0030] The beneficial effects of the present invention are:

[0031] Under the action of an initiator and an emulsifier, with water as a solvent, methyl methacrylate and butyl methacrylate are first polymerized into a core phase, and then under the action of an initiator and an emulsifier, methyl methacrylate, butyl methacrylate, octadecyl methacrylate, hydroxyethyl methacrylate, and fluorinated methacrylate undergo a polymerization reaction to obtain the fluorinated acrylate polymer emulsion. The preparation method of the present invention has a simple process, good repeatability, and low raw material price. The prepared polymer has low surface free energy and excellent hydrophobicity, and can achieve both economy and functionality.

[0032] The fluorine-containing acrylate polymer emulsion disclosed in the present invention combines with the surface of the substrate by using active groups, which significantly enhances the adhesion of the obtained coating while maintaining excellent hydrophobic properties, and further reduces the cost.

[0033] The invention specifically uses methyl methacrylate, butyl methacrylate, octadecyl methacrylate, hydroxyethyl methacrylate and a fluorine-containing acrylate monomer with a short fluorocarbon chain as monomers for emulsion polymerization to carry out polymerization reaction to obtain a fluorine-containing acrylate polymer emulsion. Methyl methacrylate and butyl methacrylate are selected as core structures. The copolymer of the two has certain weather resistance and chemical resistance, ensuring that the polymer has certain stability. The structures of hydroxyethyl methacrylate and octadecyl methacrylate are introduced into the molecule, reducing the usage of the fluorine-containing unsaturated monomer, reducing the cost of the polymer system to a certain extent, and enhancing the adhesion of the obtained coating while maintaining excellent hydrophobic performance. Methyl methacrylate is low in price, and its addition into the system reduces the cost. The obtained coating of the invention has strong adhesion, simple process, low price, good repeatability, low surface free energy and excellent hydrophobic performance, and can achieve both economy and functionality. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1is the H NMR spectrum of the fluorinated monomer FMA in Example 1 of the present invention;

[0035] Figure 2 The infrared spectra of the fluorocarbon polymer PFA1, the fluorinated monomer FMA and the polymer PA prepared in Example 1 of the present invention;

[0036] Figure 3 The water contact angles of the coatings prepared from the emulsions of the comparative examples and Examples 1-5 of the present invention are tested;

[0037] Figure 4 The water contact angles of the coatings prepared after emulsion modification in the comparative example and Example 6 of the present invention are tested. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0040] Comparative Example 1

[0041] The synthesis of fluorine-free emulsion, its core structure is as follows:

[0042]

[0043] Its shell structure is as follows:

[0044]

[0045] The synthesis process comprises the following steps: placing 1.232 g of BMA butyl methacrylate, 0.328 g of MMA methyl methacrylate, 0.04 g of DNS-86 and 1.5 ml of deionized water in a beaker and stirring vigorously for 30 minutes to form a pre-emulsified core emulsion; adding 0.528 g of BMA butyl methacrylate, 0.396 g of MMA methyl methacrylate, 0.035 g of HEMA hydroxyethyl methacrylate, 0.5 g of SMA octadecyl methacrylate, 0.04 g of DNS-86 and 1.5 ml of deionized water into a container and stirring vigorously for 30 minutes to form a pre-emulsified shell emulsion; and adding 1 / 3 of the pre-emulsified core emulsion, 1 / 3 of the APS solution, 0.04 g of DNS-86 and 3 ml of deionized water into a 50 ml three-necked flask equipped with a reflux condenser. The reaction was carried out at 60°C for 20 minutes, then the temperature was raised to 70°C, 1 / 3 of the APS solution and the remaining pre-emulsified core emulsion were added dropwise to the system, and the system continued to react for 2 hours; the pre-emulsified shell emulsion and the remaining 1 / 3 of the APS solution were added to a three-necked flask, polymerized at 70°C for 2 hours, and the pH was adjusted to 8-9 with ammonia water. A milky white liquid PA was obtained, and its weight average molecular weight was 2.01×10 5 .

[0046] Example 1

[0047] This embodiment provides a method for preparing a fluorinated acrylic polymer emulsion;

[0048] Among them, the synthesis of fluorinated acrylate monomer methacrylate 4,4,5,5,6,6,6-heptafluoro-3,3-ditrifluoromethyl-hexyl ester (FMA):

[0049] Its structural formula is shown in the figure below:

[0050]

[0051] The synthesis steps include the following steps: in a three-necked flask under argon protection, 3.64g of fluorinated alcohol and 1.21g of triethylamine are added to 10ml of dichloromethane, and then 0.94g of methacryloyl chloride is slowly dripped in an ice-water bath, and reacted at room temperature for 8h, the liquid obtained by the reaction is quenched with 5wt% sulfuric acid, the organic phase is washed with deionized water and saturated NH4Cl solution, and then dried with anhydrous sodium sulfate, filtered, concentrated by spin drying, and separated and purified by column chromatography (petroleum ether: ethyl acetate = 200:5) to obtain a colorless transparent liquid product; wherein the structural formula of the fluorinated alcohol is Prepared by the laboratory according to the preparation method;

[0052] Preparation of fluorinated emulsion PFA1, its core structure is consistent with PA, and its shell structure is as follows:

[0053]

[0054] The preparation method comprises the following steps: placing 1.232g of BMA butyl methacrylate, 0.328g of MMA methyl methacrylate, 0.04g of emulsifier DNS-86 and 1.5ml of deionized water in a beaker and stirring vigorously for 30min to form a pre-emulsified core emulsion; adding 0.528g of BMA butyl methacrylate, 0.396g of MMA methyl methacrylate, 0.035g of HEMA hydroxyethyl methacrylate, 0.5g of SMA octadecyl methacrylate, 0.1g of FMA, 0.04g of DNS-86 and 1.5ml of deionized water into a container and stirring vigorously for 30min to form a pre-emulsified shell emulsion; adding 1 / 3 of the pre-emulsified core emulsion, 1 / 3 of the initiator APS solution and 0.04g of the initiator APS solution into a 50ml three-necked flask equipped with a reflux condenser, DNS-86 and 3 ml of deionized water were reacted at 60 ° C for 20 min, then the temperature was raised to 70 ° C, 1 / 3 of the initiator APS solution and the remaining pre-emulsified core emulsion were added dropwise to the system, and the system continued to react for 2 h; the pre-emulsified shell emulsion and the remaining 1 / 3 of the initiator APS solution were added to a three-necked flask, polymerized at 70 ° C for 2 h, and the pH was adjusted to 8-9 with ammonia water to obtain a milky white liquid PFA1, and the weight-average molecular weight of the polymer was 1.73×10 5 , in the structural formula, m=80, n=80, a=15, b=6, c=5.

[0055] The H NMR spectrum and IR spectrum of the fluorinated monomer FMA (4,4,5,5,6,6,6-heptafluoro-3,3-ditrifluoromethyl-hexyl methacrylate) in Example 1 of the present invention, the IR spectrum of the fluorocarbon polymer PFA1 and the polymer PA prepared in Comparative Example 1 are as follows: Figure 1 Figure 2 shown.

[0056] Example 2

[0057] This embodiment provides a method for preparing a fluorinated emulsion PFA2, whose core structure is consistent with that of PA, and whose shell structure is as follows:

[0058]

[0059] The preparation method comprises the following steps: placing 1.232 g of BMA butyl methacrylate, 0.328 g of MMA methyl methacrylate, 0.04 g of DNS-86 and 1.5 ml of deionized water in a beaker and stirring vigorously for 30 minutes to form a pre-emulsified core emulsion; adding 0.528 g of BMA butyl methacrylate, 0.396 g of MMA methyl methacrylate, 0.035 g of HEMA hydroxyethyl methacrylate, 0.5 g of SMA octadecyl methacrylate, 0.2 g of FMA, 0.04 g of DNS-86 and 1.5 ml of deionized water into a container and stirring vigorously for 30 minutes to form a pre-emulsified shell emulsion; adding 1 / 3 of the pre-emulsified core emulsion, 1 / 3 of the APS solution, 0.04 g of the pre-emulsified shell emulsion into a 50 ml three-necked flask equipped with a reflux condenser; DNS-86 and 3 ml of deionized water were reacted at 60°C for 20 min, then the temperature was raised to 70°C, 1 / 3 of the APS solution and the remaining pre-emulsified core emulsion were added dropwise to the system, and the system continued to react for 2 h; the pre-emulsified shell emulsion and the remaining 1 / 3 of the APS solution were added to a three-necked flask, polymerized at 70°C for 2 h, and the pH was adjusted to 8-9 with ammonia water. A milky white liquid PFA2 was obtained, and the weight average molecular weight of the polymer was 1.71×10 5 , in the structural formula, m=80, n=80, a=15, b=6, c=10.

[0060] Example 3

[0061] This embodiment provides a method for preparing a fluorinated emulsion PFA3, whose core structure is consistent with that of PA, and whose shell structure is as follows:

[0062]

[0063] The preparation method comprises the following steps: placing 1.232 g of BMA butyl methacrylate, 0.328 g of MMA methyl methacrylate, 0.04 g of DNS-86 and 1.5 ml of deionized water in a beaker and stirring vigorously for 30 minutes to form a pre-emulsified core emulsion; adding 0.528 g of BMA butyl methacrylate, 0.396 g of MMA methyl methacrylate, 0.035 g of HEMA hydroxyethyl methacrylate, 0.5 g of SMA octadecyl methacrylate, 0.3 g of FMA, 0.04 g of DNS-86 and 1.5 ml of deionized water into a container and stirring vigorously for 30 minutes to form a pre-emulsified shell emulsion; adding 1 / 3 of the pre-emulsified core emulsion, 1 / 3 of the APS solution, 0.04 g of the pre-emulsified shell emulsion into a 50 ml three-necked flask equipped with a reflux condenser; DNS-86 and 3 ml of deionized water were reacted at 60 ° C for 20 min, then the temperature was raised to 70 ° C, 1 / 3 of the APS solution and the remaining pre-emulsified core emulsion were added dropwise to the system, and the system continued to react for 2 h; the pre-emulsified shell emulsion and the remaining 1 / 3 of the APS solution were added to a three-necked flask, polymerized at 70 ° C for 2 h, and the pH was adjusted to 8-9 with ammonia water to obtain a milky white liquid PFA3, and the weight-average molecular weight of the polymer was 2.24×10 5 , in the structural formula, m=80, n=80, a=15, b=6, c=15.

[0064] Example 4

[0065] This embodiment provides a method for preparing a fluorinated emulsion PFA4, whose core structure is consistent with that of PA, and whose shell structure is as follows:

[0066]

[0067] The preparation method comprises the following steps: placing 1.232 g of BMA butyl methacrylate, 0.328 g of MMA methyl methacrylate, 0.04 g of DNS-86 and 1.5 ml of deionized water in a beaker and stirring vigorously for 30 minutes to form a pre-emulsified core emulsion; adding 0.528 g of BMA butyl methacrylate, 0.396 g of MMA methyl methacrylate, 0.035 g of HEMA hydroxyethyl methacrylate, 0.5 g of SMA octadecyl methacrylate, 0.4 g of FMA, 0.04 g of DNS-86 and 1.5 ml of deionized water into a container and stirring vigorously for 30 minutes to form a pre-emulsified shell emulsion; adding 1 / 3 of the pre-emulsified core emulsion, 1 / 3 of the APS solution, 0.04 g of the pre-emulsified shell emulsion into a 50 ml three-necked flask equipped with a reflux condenser; DNS-86 and 3 ml of deionized water were reacted at 60 ° C for 20 min, then the temperature was raised to 70 ° C, 1 / 3 of the APS solution and the remaining pre-emulsified core emulsion were added dropwise to the system, and the system continued to react for 2 h; the pre-emulsified shell emulsion and the remaining 1 / 3 of the APS solution were added to a three-necked flask, polymerized at 70 ° C for 2 h, and the pH was adjusted to 8-9 with ammonia water to obtain a milky white liquid PFA4, and the weight-average molecular weight of the polymer was 3.5×10 5 , in the structural formula, m=80, n=80, a=15, b=6, c=20.

[0068] Example 5

[0069] This embodiment provides a method for preparing a fluorinated emulsion PFA5, whose core structure is consistent with that of PA, and whose shell structure is as follows:

[0070]

[0071] The preparation method comprises the following steps: placing 1.232g of BMA butyl methacrylate, 0.328g of MMA methyl methacrylate, 0.04g of DNS-86 and 1.5ml of deionized water in a beaker and stirring vigorously for 30min to form a pre-emulsified core emulsion; adding 0.528g of BMA butyl methacrylate, 0.396g of MMA methyl methacrylate, 0.035g of HEMA hydroxyethyl methacrylate, 0.5g of SMA octadecyl methacrylate, 0.5g of fluorinated monomer FMA, 0.04g of DNS-86 and 1.5ml of deionized water into a container and stirring vigorously for 30min to form a pre-emulsified shell emulsion; adding 1 / 3 of the pre-emulsified core emulsion, 1 / 3 of the APS solution, 0.04g of the pre-emulsified shell emulsion into a 50ml three-necked flask equipped with a reflux condenser; DNS-86 and 3 ml of deionized water were reacted at 60 ° C for 20 min, then the temperature was raised to 70 ° C, 1 / 3 of the APS solution and the remaining pre-emulsified core emulsion were added dropwise to the system, and the system continued to react for 2 h; the pre-emulsified shell emulsion and the remaining 1 / 3 of the APS solution were added to a three-necked flask, polymerized at 70 ° C for 2 h, and the pH was adjusted to 8-9 with ammonia water to obtain a milky white liquid PFA5, and the weight-average molecular weight of the polymer was 2.13×10 5 , in the structural formula, m=80, n=80, a=15, b=6, c=25.

[0072] The polymer emulsions prepared in the examples and comparative examples were subjected to a hydrophobic test;

[0073] The polymer emulsions prepared in Examples 1 to 5 and Comparative Example 1 were respectively mixed with ethyl acetate to form solutions with a mass concentration of 5% to obtain coating solutions. The preparation method of the glass slide is as follows: the glass slide is immersed in ethanol for cleaning, and then taken out with clean tweezers, dried in an oven, and allowed to cool to room temperature. The coating method is as follows: the coating solution is loaded into a spray can, and sprayed evenly at a distance of 20 cm from the glass slide at a pressure of 200 kPa, and the sprayed glass slide is baked in an oven at 100°C for 2 h. According to the above preparation method, 3 coated glass slides are prepared for each solution.

[0074] The contact angle between the membrane and water was tested separately. Each solution was measured three times and the average value was taken. The test conditions were: liquid volume 3 μl, height 0.5 cm, magnification 7 times, and the results were as follows: Figure 3 As shown in Table 1 below;

[0075] Table 1 Hydrophobicity test data of coatings prepared from polymer emulsions prepared in Examples and Comparative Examples

[0076]

[0077]

[0078] As shown in Table 1, when the contact angle is used as an indicator for evaluating hydrophobicity, it can be seen from the sample test results of Comparative Example 1 and each embodiment that when the fluorinated monomer FMA is not added, the water contact angle of the coating is 94.4°, which is close to the hydrophobic state. After the fluorinated monomer FMA is added, the contact angle is increased to 101.3°, and it continues to increase to 107.1° with the increase of the content of the fluorinated monomer FMA. This is because the fluorinated polymer has a lower surface energy, and its hydrophobic property is better than that of the fluorinated polymer, and the macroscopic performance is a larger water contact angle; and the polymer structure of the present invention has a short fluorine chain, and the number of carbon fluorine atoms in the fluorinated acrylate monomer is 6, but the number of straight carbon atoms in the fluorocarbon chain is only 3. Compared with the reference (CN104788608A), the present invention introduces hydroxyl hydrogen bonding, and the adhesion is greatly improved. Compared with the reference (CN110540614A), the straight chain in the fluorocarbon chain of the present invention is shorter, which can greatly improve the environmental safety characteristics.

[0079] Example 6

[0080] The present embodiment provides a coating, which is made of a modified polymer emulsion. The polymer emulsion prepared in Example 4 of the present invention is mixed and compounded with silica sol and isocyanate curing agent to obtain a coating material. The specific steps are as follows: 0.3g of the polymer emulsion is mixed with ethyl acetate to prepare a solution with a mass concentration of 5%, different proportions of silica sol and 0.03g of isocyanate curing agent are added, and the solution is uniformly dispersed in ultrasound for 20 minutes to obtain a silica sol-modified polymer emulsion, which is then coated and dried to obtain a coating.

[0081] The modified polymer emulsion was subjected to a hydrophobicity test;

[0082] The preparation method of the glass slide is as follows: the glass slide is immersed in ethanol for cleaning, then taken out with clean tweezers, dried in an oven, and allowed to cool to room temperature. The coating method is as follows: the coating solution is placed in a spray can, and sprayed evenly at a distance of 20 cm from the glass slide at a pressure of 200 kPa, and the sprayed glass slide is baked in an oven at 100 ° C for 2 hours. According to the above preparation method, 3 coated glass slides are prepared for each solution, and the contact angle between the film and water is tested respectively. Each solution is measured three times, and the average value of the three times is taken. The test conditions are: liquid volume 3 μL, height 0.5 cm, magnification 7 times; the results are as follows Figure 4 and as described in Table 2 below:

[0083] Table 2 Hydrophobicity test data of the coating prepared after modification of the polymer emulsion prepared in Example 4

[0084]

[0085]

[0086] When the contact angle is used as an indicator for evaluating hydrophobicity, it can be seen from Table 2 above that before modification without adding silica sol, the water contact angle of the coating can only reach 104.2, and the hydrophobicity needs to be improved. After modification with silica sol, the polymer emulsion of the present application exhibits excellent hydrophobic properties when modified with a silica sol of greater than 0.4 mass ratio, and its water contact angle is greater than 140°. In addition, the polymer emulsion of the present application exhibits super hydrophobic properties when modified with a silica sol of 0.8 mass ratio, and its water contact angle is 152.3°, which is greater than the water contact angle evaluation standard of 150° for super hydrophobic surfaces.

[0087] The polymer emulsion prepared by the present invention reduces the cost of the polymer system to a certain extent, and enhances the adhesion of the obtained coating while maintaining excellent hydrophobic properties; the coating obtained by the present invention or the modified coating has strong adhesion, simple process, low price, good repeatability, low surface free energy and excellent hydrophobic properties, and can achieve both economy and functionality.

[0088] In addition to the above embodiments, the present invention may also have other implementation modes. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention.

Claims

1. A fluorinated acrylic polymer emulsion, characterized in that: The fluorinated acrylic polymer emulsion has a core-shell structure, and its core phase is a polymer having a general chemical structure formula: Wherein, R is hydrogen or methyl, R1 is selected from any one of C1 to C18 alkyl groups, m=30 to 80, n=10 to 30; The shell phase is a polymer with the following chemical structure: Wherein, R is hydrogen or methyl, R1 is selected from any one of C1~C18 alkyl groups, R2 is selected from any one of C12~C18 alkyl groups, Rf is a group having a C(CF3)2CF2CF2CF3 structure, m=10~100, n=10~100, a=5~15, b=1~10, c=2~30.

2. The fluorinated acrylic polymer emulsion according to claim 1, characterized in that: The weight average molecular weight of the polymer is 1.7×10 5 ~3.5×10 5 .

3. The method for preparing the fluorinated acrylic polymer emulsion according to claim 1 or 2, characterized in that: The specific steps include: Under the action of initiator and emulsifier, water is used as solvent, and the The two acrylic ester monomers are polymerized into a core phase polymer, and then under the action of an initiator and an emulsifier, the core phase polymer is expressed as The acrylic acid ester monomer is represented by Hydroxyethyl acrylate and represented by The fluorinated acrylate monomer is polymerized on the surface of the core phase polymer to form a shell phase polymer, thereby obtaining a fluorinated acrylate polymer emulsion with a core-shell structure.

4. The method for preparing the fluorinated acrylic polymer emulsion according to claim 3, characterized in that: It is expressed as The acrylic acid ester monomer is selected from any one of methyl methacrylate, ethyl methacrylate, butyl methacrylate, hexyl methacrylate, isooctyl methacrylate, lauryl methacrylate, octadecyl methacrylate, methyl acrylate, ethyl acrylate, butyl acrylate, hexyl acrylate, isooctyl acrylate, lauryl acrylate and octadecyl acrylate; It is expressed as The acrylic acid ester monomer is selected from any one of lauryl methacrylate, octadecyl methacrylate, lauryl acrylate and octadecyl acrylate.

5. The method for preparing the fluorinated acrylic polymer emulsion according to claim 3, characterized in that: The initiation temperature is 30-100°C, the polymerization temperature is 30-200°C, and the time is 5-20h.

6. The method for preparing the fluorinated acrylic polymer emulsion according to claim 3, characterized in that: The initiator is used in an amount of 0.1-5% of the total weight of the acrylic ester monomer; the initiator is a mixture of one or more of azo compounds, inorganic peroxides, and organic peroxides; the emulsifier is selected from at least one of anionic emulsifiers, nonionic emulsifiers, and cationic emulsifiers.

7. The method for preparing the fluorinated acrylic polymer emulsion according to claim 3, characterized in that: It is expressed as The acrylic acid ester monomer is selected from octadecyl methacrylate, and the weight ratio of the fluorinated methacrylate monomer to octadecyl methacrylate is 1:1-1:5; the mass ratio of the fluorinated methacrylate monomer to hydroxyethyl acrylate is 20:7-100:

7.

8. The method for preparing the fluorinated acrylic polymer emulsion according to claim 3, characterized in that: It is expressed as The fluorinated acrylate monomer is prepared in the presence of a base. Obtained by reaction, X is a halogen; in: The molar ratio of the base is 1:(1-1.5):(1-1.5).

9. The method for preparing the fluorinated acrylic polymer emulsion according to claim 8, characterized in that: The base is an organic base, and the organic base is selected from any one of triethylamine, pyridine, N,N-diisopropylethylamine, diethylamine, piperidine or N-methylpiperidine; The reaction temperature is -30°C to room temperature, and the reaction solvent is any one of ethylene glycol dimethyl ether, ethyl ether, diethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, tetrahydrofuran, dichloromethane, DMF, benzene or 1,2-dichloroethane.

10. An application of the fluorinated acrylic polymer emulsion according to claim 1, characterized in that: Fluorinated acrylate polymer emulsion is used to prepare coating: The prepared fluorinated acrylic polymer emulsion is mixed with silica sol and isocyanate curing agent, and uniformly dispersed in ultrasound to obtain a silica sol-modified polymer emulsion, which is then coated on a substrate to form a coating.

Citation Information

Patent Citations

  • Fluorine-containing polymer for low-energy surface coating and preparation method of fluorine-containing polymer

    CN104788608A

  • Core-shell type short-chain fluorine-containing acrylate emulsion and preparation method thereof

    CN105440201A

  • Water-based fluorinated acrylate copolymer and hybrid membrane, and preparation methods and application thereof

    CN110540614A

  • Preparation method and application of shell-core fluorine-containing polymer nano-emulsion

    CN112830998A

  • Fluorinated core-shell-polymers and process for preparing same

    US20130171346A1